MINAT WORD OF MOUTH PADA PRODUK PERUMAHAN GRAHA PADMA SEMARANG - Tifani, Amelia Gita; Widiyanto, Ibnu (Faculty of Economics and Business Diponegoro University, 2015)
This research aimed to investigate how physical attractiveness on houses and the beauty of environment affect customer satisfaction and how the satisfaction affects the residents doing word of mouths.The samples of this research were the 320 residents of Perumahan Graha Padma in Kota Semarang using Non Probability Sampling technic. The methods of data analysis used here was quantitative analysis using reliability and validity, classic assumptions test, hypothesis test, determinant coefficients and also multiple linear regression analysis.The results showed that physical attractiveness on houses and the beauty of environment had positive effect on customer satisfactions, while physical attractiveness on houses, the beauty of environment and customer satisfaction had positive effect on word of mouth. From model 1, physical attractiveness gives positive effect on 0,373 while beauty of environment gives positive effect for 0,442 on customer satisfaction. From model 2 physical attractiveness, the beauty of environment and customer satisfaction influenced word of mouth intention around 0,434, 0,286 and 0,214. Thus implies that physical attractiveness gives biggest influence on word of mouth intention.